2016
DOI: 10.1002/adfm.201602069
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Transistors via Polyethylenimine Doping of the Channel Layer: Interplay of Doping, Microstructure, and Charge Transport

Abstract: Polymer doping of solution‐processed In2O3 with small amounts of the electron‐rich polymer, polyethylenimine (PEI), affords superior transistor performance, including higher electron mobility than that of the pristine In2O3 matrix. PEI doping of In2O3 films not only frustrates crystallization and controls the carrier concentration but, more importantly, acts as electron dopant and/or scattering center depending on the polymer doping concentration. The electron donating capacity of PEI combined with charge trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 69 publications
11
114
0
Order By: Relevance
“…[26] In another report, Huang et al showed that PEI can n-dope and tune the performance of In 2 O 3 -based www.advelectronicmat.de Adv. [27] These results are consistent with our finding that PEI is a strong n-type dopant. Mater.…”
Section: Wileyonlinelibrarycomsupporting
confidence: 93%
“…[26] In another report, Huang et al showed that PEI can n-dope and tune the performance of In 2 O 3 -based www.advelectronicmat.de Adv. [27] These results are consistent with our finding that PEI is a strong n-type dopant. Mater.…”
Section: Wileyonlinelibrarycomsupporting
confidence: 93%
“…Nevertheless, solution‐processing of MO precursors holds significant promise for lower cost production and compatibility with flexible substrates . In this regard, indium oxide (In 2 O 3 ) is one of the most investigated solution‐processed oxide semiconductors, however, the carrier density of pristine In 2 O 3 is difficult to control and In 2 O 3 films are usually polycrystalline, limiting their performance uniformity over large areas as well as mechanical flexibility . To address both of these issues, metals such as Zn and/or Ga are added to In 2 O 3 , enabling the growth of amorphous MO thin films with enhanced electronic properties and ultimately affording far more stable TFT characteristics …”
Section: Performance Metrics Of the Indicated Tft Devices On Si/sio2 mentioning
confidence: 99%
“…PEI has been applied as an effective n‐type dopant to increase the mobility of n‐type metal oxide and polymer in FETs. [54a,65] PEI is introduced to dope metal oxide and indium oxide (In 2 O 3 ) to enhance the transistor performance especially the mobility. PEI doping of In 2 O 3 films not only impedes crystallization and controls the carrier concentration, but also acts as electron dopants and/or scattering centers.…”
Section: Applications In Optoelectronic Devicesmentioning
confidence: 99%
“…Except for the metal oxide, PEI plays a more apparent role in doping the polymer semiconductor. [65c] Nanopores enhanced n‐doping of polymer poly(diketopyrrolopyrrole‐thiophene‐thieno[3,2,b]thiophenethiophene) (DPP2T‐TT) doped by PEI has been demonstrated. Doping with PEI at a high concentration enhances the n‐channel characteristics via passivating the p‐channel behavior.…”
Section: Applications In Optoelectronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation